KAJIAN NILAI DAYA DUKUNG TANAH DASAR MENGGUNAKAN DYNAMIC CONE PENETROMETER DAN CBR IN PLACE - Azwarman Azwarman (Universitas Batanghari Jambi, 2015)
In road construction, there is a need to assess the adequacy of the subgrade to behave satisfactorily beneath a pavement. The adequacy usually representated as California Bearing Ratio (CBR) value. In-situ penetration tests have been widely used in geotechnical and foundation engineering for site investigation in support of analysis and design.The CBR in-place is typical in-situ penetration test. While the Dynamic Cone Penetration Test (DCPT), relatively cost cheaper than CBR in-place test, could give the CBR value through formulas stated by researchers.This paper presented the comparison of CBR values found from CBR in-place test and DCP test along 22,4 km of road construction at WKS road, Merlung Region of Jambi Province.The result shown the same trend of CBR value of both methods. However, difference between two test method will result in different of segment CBR as use for pavement design. Based on minimum criterion, the minimum result should be use in design.Key words: daya dukung subgrade, CBR In-Place, DCP Test